(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To assess the functional and radiological outcome of segmental transport by Ilizarov fixation in case of bone loss in tibia. Methods: This descriptive study was conducted at King Abdullah Teaching Hospital, Mansehra from 1st January 2016 to 31st February 2019 and comprised 20 patients. Patients fulfilling the inclusion criteria were fixed with were Ilizarove fixator and followed for bone union and functional outcome. Results: A total of 20 patients with mean age 36.80+8.49 years (range 26-52 years) were included in our study. Male patients were16 (80%) while 4 (20%) were females. The mean tibial gap was 6.05+4.14 cm (range 1.5-13.5 cm) and mean period of Ilizarov treatment was 7.30+1.94 months (range 5-10 months) while mean follow-up was 30.80+7.19 months (range 20-38 months). Post op results were excellent in 6 (30.0%) patients, good in 8 (40%) patients and fair in 6 (30%) patients. Conclusion: Cases of tibial bone loss treated with Ilizarov produce excellent to good functional and radiological results in majority of patients.